Simvastatin modulates cellular components in influenza A virus-infected cells - Mehrbod, Parvaneh; Bejo, Mohd Hair; Tengku Ibrahim, Tengku Azmi; Omar, Abdul Rahman; El Zowalaty, Mohamed Ezzat; Ajdari, Zahra; Ideris, Aini (Spandidos Publications, 2014)
Influenza A virus is one of the most important health risks that lead to significant respiratory infections. Continuous antigenic changes and lack of promising vaccines are the reasons for the unsuccessful treatment of influenza. Statins are pleiotropic drugs that have recently served as anti-influenza agents due to their anti-inflammatory activity. In this study, the effect of simvastatin on influenza A-infected cells was investigated. Based on the MTT cytotoxicity test, hemagglutination (HA) assay and qPCR it was found that simvastatin maintained cell viability and decreased the viral load significantly as compared to virus-inoculated cells. The expression of important pro-inflammatory cytokines (tumor necrosis factor-α, interleukin-6 and interferon-γ), which was quantified using ELISA showed that simvastatin decreased the expression of pro-inflammatory cytokines to an average of 2-fold. Furthermore, the modulation of actin filament polymerization was determined using rhodamine staining. Endocytosis and autophagy processes were examined by detecting Rab and RhoA GTPase protein prenylation and LC3 lipidation using western blotting. The results showed that inhibiting GTPase and LC3 membrane localization using simvastatin inhibits influenza replication. Findings of this study provide evidence that modulation of RhoA, Rabs and LC3 may be the underlying mechanisms for the inhibitory effects of simvastatin as an anti-influenza compound.